Holy Triune Love: A Reformulation of Divine Simplicity - Sean Luke (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
In this paper, I formulate an alternative to the classical doctrine of divine simplicity. Simply stated, God’s nature is best understood as Holy Triune Love (HTL), and all attributes are best understood as aspects of HTL. This reformulation will allow us to affirm much of the content of classical simplicity without the actus-purus doctrine. This paper will proceed as follows. First, I will define CS and sketch its rationale in God's metaphysical ultimacy. Second, I will defend two critical objections from the incarnation and divine knowledge I take to be decisive against CS. Third, I will sketch HTL in relation to the trinitarian processions and the attributes, showing how HTL best satisfies the doctrinal motivations for CS. Fourth, I will show how HTL responds to the challenges I’ve raised against CS. I will then conclude by answering five potential objections.